Relationship Between The Black Cocoa Ant, Dolichoderus Thoracicus Smith (Hymenoptera: Formicidae) and the Cocoa Pod Borer, Conopomorpha Cramerella Snellen(Lepidoptera: Gracillarlldae) in a Cocoa-Coconut Ecosystem - See, Yee Ai (1996)
The relationship between the black cocoa ant Dolichoderus thoracicus Smith (Hymenoptera: Formicidae) and the cocoa pod borer Conopomorpha cramerella Snellen (Lepidoptera: Gracillariidae) was studied in a cocoa-coconut field. D. thoracicus was present in moderate to high abundance in the field at the beginning of the experiments. In one treatment, the D. thoracicus population was depressed with insecticides (ant-scarce plots) and was augmented in the other treatment by the provision of artificial nests and dried leaf shelters (ant-abundant plots). percentage of C. cramere/la infestation in ant-abundant plots was generally less than 50% while the reverse was true in ant-scarce plots. Even though there was no significant difference in the percentage of pods which were infested and extractable as well as partially extractable, the percentage of unextractable pods in ant-abundant plots was significantly lower than in ant-scarce plots, indicating that D. thoracicus reduced the severity of C. cramerella infestation. This difference was evident throughout the trial. Mammalian damage was also more pronounced in ant-scarce plots. In a survey of the relationship between D. thoracicus pod abundance and C. cramerella infestation conducted within and outside the trial area, the two were found to be negatively related. Pods within the trial plots also had less C. cramerella damage compared to those outside the trial plots, indicating a possible attrition effect. Pods from which D. thoracicus were deliberately excluded also had a higher incidence of infestation compared to pods on which D. thoracicus was enhanced. Moderate D. thoracicus abundance on pods was sufficient to prevent C. cramerella infestation. The mechanism of control was probably deterrence of C. cramere/la oviposition. This study shows that encouraging D. thoracicus is beneficial to cocoa as it reduces the damage of two major pests, C. cramerella and mammals.